Predictors of Prenatal Depression: A Cross-Sectional Study in Rural Pakistan - Khan, Rukhsana; Waqas, Ahmed; Mustehsan, Zille Huma; Khan, Amna Saeed; Sikander, Siham; Ahmad, Ikhlaq; Jamil, Anam; Sharif, Maria; Bilal, Samina; Zulfiqar, Shafaq; Bibi, Amina; Rahman, Atif (Frontiers in Psychiatry, 2021)
Objective: To determine the prevalence and association of prenatal depression with socioeconomic, demographic and personal factors among pregnant women living in Kallar Syedan, Rawalpindi, Pakistan. Methods: Five hundred women in the second and third trimester of pregnancy, living in Kallar Syedan, a rural area of district Rawalpindi Pakistan, were included in the study. Depression was assessed using “Patient health questionnaire” (PHQ9) in Urdu, with a cut-off score of 10. Multi-dimensional scale of perceived social support (MSPSS) was used to assess perceived social support. Life Events and Difficulties Schedule (LEDS) were used to measure stressful life events in past 1 year. Tool to assess intimate partner violence (IPV) was based on WHO Multi Country Study on “Women's Health and Domestic Violence against Women.” Results: Prevalence of prenatal depression was found to be 27%. Number of pregnancies was significantly associated with prenatal depression (p < 0.01). Women living in a joint family and those who perceived themselves as moderately satisfied or not satisfied with their life in the next 4 years were found to be depressed (p < 0.01, OR 6.9, CI 1.77–26.73). Depressive symptomatology in women who experienced more than five stressful life events in last 1 year was three times higher (p < 0.001, OR 3.2, CI 1.68–5.98) than in women with 1–2 stressful events. Women who were supported by their significant others or their family members had 0.9 times (p < 0.01, OR 0.9, CI 0.85–0.96) less chance of getting depressed. Pregnant women who were psychologically abused by their partners were 1.5 times more depressed (p < 0.05 CI 1.12–2.51). Odds of having depression was also high in women who had less mean score of MSSI (p < 0.05, OR 1.1, CI 1.01–1.09). Women who had suitable accommodation had 0.5 times less chance of having depression than others (p < 0.05, OR 0.5, CI 0.27–0.92). Conclusion: Over a quarter of the women in the study population reported prenatal depression, which were predicted predominantly by psychosocial variables.